Association between ECG Alterations and Outcomes of Patients with Acute Organophosphate Poisoning - Kavous Shahsavari Nia; Payman Moharamzadeh; Ali Taghizadieh; Samira Abedi; Afshin Gharekhani (Tabriz University of Medical Sciences, 2021)
Background: Organophosphate (OP) poisoning leads to atrioventricular node blockade, alterations in ST segment, prolongation of QT interval, alterations in P wave, lethal arrhythmias, and cardiac arrest through the inhibition of acetylcholinesterase and consequent accumulation of free synaptic acetylcholine level. So the present study was aimed to investigate the role of electrocardiographic (ECG) monitoring combined with the introduction of anti-arrhythmic interventions on OPs poisoning outcomes. Methods: 41 patients with OPs poisoning were included. Patients with history of heart or liver diseases, cholinesterase deficiency, anemia, and poisoning with other toxins were excluded. Demographic characteristics, the time elapsed between OP ingestion and hospital admission, need for mechanical ventilation, and serum cholinesterase level were recorded. ECG of patients was analyzed for rate, rhythm, ST-T abnormalities, conduction defects, and measurement of PR and QT intervals. Study outcomes were measures of morbidity and mortality. Results: Of 41 patients, with mean age of 34.76±13 years, 19 were male. For 68.3% of the patients, the time elapsed between ingestion and hospital admission was 3-6 hours. Eight patients were treated with mechanical ventilation. There was a significant correlation between ST segment alterations and poisoning outcomes including uncomplicated discharge, complicated discharge, and death (P=0.02). Thirty one patients were discharged without any complication, 8 with morbidity and 2 expired. ST segment changes were seen in 4 patients. Two percent had PR interval greater than 0.21s and 3% had QT interval longer than 0.45s. The mean serum cholinesterase concentration was 3011.56 U/L. Conclusion: Due to lethal cardiac arrhythmia caused by OP poisoning, continuous monitoring, managing, and preventing irreparable effects of OP poisoning is highly emphasized.